Therapists’ emotional state after sessions in which suicidality is addressed: need for improved management of suicidal tendencies in patients with borderline personality pathology - Bühlmann, Vera; Schlüter-Müller, Susanne; Fürer, Lukas; Steppan, Martin; Birkhölzer, Marc; Schmeck, Klaus; Koenig, Julian; Kaess, Michael; Zimmermann, Ronan (BMC psychiatry, 2021)
Patient suicidality is a frequently experienced topic for psychotherapists. Especially adolescents with borderline personality pathology (BPP) often exhibit suicidal tendencies. Previous research which examined therapists’ countertransference towards suicidal patients suggested that therapists are negatively affected and distressed by them. We hypothesize that this emotional response of the therapists is related to specific sessions in which suicidality came up as a topic. Accordingly, the objective of this study consists in examining therapists’ emotional state on a session level of analysis.